Utilizing telemedicine during COVID-19 pandemic for a low-threshold, street-based buprenorphine program. (1st January 2022) - Harris, Robert; Rosecrans, Amanda; Zoltick, Meredith; Willman, Catherine; Saxton, Ronald; Cotterell, Margaret; Bell, Joy; Blackwell, Ingrid; Page, Kathleen R.
Abstract: Background: Changes in federal policy during the COVID-19 pandemic allowing for the use of telemedicine to treat opioid use disorder (OUD) have facilitated innovative strategies to engage and retain people in treatment. Since 2018, the Baltimore City Health Department has operated a mobile street medicine program called Healthcare on The Spot (The Spot) that provides treatment for OUD and infectious diseases. This study describes the transition of The Spot's buprenorphine service to telemedicine during the COVID-19 pandemic and one year treatment retention. Methods: Patients actively engaged in care at the time of transition to telemedicine and patients newly engaged in buprenorphine services through telemedicine were included in this descriptive analysis and assessed at one year for retention. Results: From March 16, 2020 to March 15, 2021, The Spot provided voice-only buprenorphine treatment services to 150 patients, 70.7% (n = 106) male and 80.0% (n = 120) Black; 131 were patients who transitioned from in person services and 19 were newly engaged via telemedicine. 80.7% (n = 121) of patients remained engaged in treatment at one year, 16.0% (n = 24) were lost to follow-up, and 3.3% (n = 5) were deceased. Patients newly engaged via telemedicine were more likely to be female and white than those retained from in person services. Conclusion: The Spot's transition of patients from a street medicine program to telemedicine during the COVID-19 pandemic has implications for future practice. Increased flexibility of service delivery, extended prescription length, and decreased UDT likely contributed to high retention rates and should inform the future structure of low-threshold buprenorphine programs. Highlights: Telemedicine can drive innovations in OUD service delivery. 80% of patients were retained in telemedicine buprenorphine treatment at one year. Majority of patients were male and African American. Decreased toxicology screening likely led to higher retention rates.